Chinese arts and crafts history, techniques and legends - Hang Jian; Guo Qiuhui (Beijing China Intercontinental Press, 2010)
This illustrated introduction discusses the colorful history and development of distinctive Chinese crafts, including ceramics, furniture, clothing and decorative arts.
The traditional arts and crafts of China -- Materials for daily use -- Textiles -- Homewares -- Decoration -- Plays and playing -- Commercial arts -- Legends related to arts and crafts -- Traditional crafts in modern China -- Chronological table of Chinese dynasties.
Keywords: Decorative arts -- China; Handicraft -- China -- History